Pengaruh Green Awareness dan Green Knowledge Generasi Z Terhadap Minat Menggunakan Layanan Perbankan Hijau yang Terdaftar di BEI - Westi Ana Lovi Ani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of green awareness and green knowledge of Generation Z on their interest in using green banking services in Indonesia, especially banks listed on the Indonesia Stock Exchange (IDX). Using Partial Least Squares-Structural Equation Modeling (PLS-SEM) analysis, it was found that green awareness and green knowledge have a positive and significant influence on interest in using green banking services. These results suggest that the higher Generation Z's level of green awareness and green knowledge about green banking, the more likely they are to use the service. This study provides implications for the banking industry in improving education and promotion strategies related to green banking.